Organizational and economic mechanism for the participation of biotechnological scientific and industrial clusters in the implementation of import substitution programs - D. V. Morozov (Путеводитель предпринимателя)
The main trends in the development of the biotechnological industry at the global level are considered. An organizational and economic mechanism for the participation of the biotechnological scientific and industrial cluster in the implementation of programs for import substitution and the transition to import advance is proposed.